PEMAAFAN SEBAGAI ALTERNATIF PENYELESAIAN TINDAK PIDANA (Telaah Integrasi Psikologi dan Hukum) - Bahrul Fawaid; Qurnia Fitriyatinur (Fakultas Hukum Universitas Wahid Hasyim, 2020)
This research seeks to explore the relationship between psychology and law, namely how psychology can provide new perspective in the field of law. Furthermore, this study wants to find out how the forgiveness process takes place and what factors influence it, as well as how forgiveness can be an alternative settlement of crime. This research is an empirical normative legal research using a conceptual approach. This research produces several findings, firstly there is a common thread between psychology and law that makes them complementary to human life. Secondly, forgiveness is a personal step that can be taken to make a person more easily at peace with circumstances, including in a crime. Thirdly, because it is considered beneficial, it needs a legal umbrella that explicitly regulates forgiveness as an alternative in resolving criminal acts other than imprisonment.